How does digital economy development influence urban land green efficiency? evidence from China - Jiang, Huayu; Xiang, Shang; Shin, Yeon-Soo (Frontiers in Environmental Science, 2025)
Rapid digital economy development is reshaping urban governance and resource allocation, but its impact on urban land green use efficiency (ULGUE) remains insufficiently examined. This study investigates whether and how digital economy development enhances ULGUE in China, focusing on direct effects, mediating mechanisms, and spatial spillovers. Using panel data from 282 prefecture-level cities during 2007–2022, ULGUE is measured with the Super-Slack-Based Measure model. The National E-Commerce Demonstration City policy serves as a quasi-natural experiment within a Differences-in-Differences framework. Complementary analyses include instrumental variable estimation, propensity score matching, and the spatial Durbin model, with robustness checks using 5G population density. Findings indicate that the digital economy and 5G infrastructure significantly improve ULGUE. Mechanism tests highlight green technology innovation and resource efficiency as key channels, with strong spatial spillover effects. Heterogeneity analysis reveals that policy impacts are strongest in eastern and early pilot cities, moderate in central regions, and weakest in western areas. Overall, the study enriches interdisciplinary research on digitalization and sustainability, and provides policy insights suggesting that region-specific green strategies and targeted digital infrastructure deployment are essential to achieve balanced and sustainable urban transitions.